1998
DOI: 10.1128/jvi.72.7.5984-5993.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Various Sendai Virus C Proteins Are Not Functionally Equivalent and Exert both Positive and Negative Effects on Viral RNA Accumulation during the Course of Infection

Abstract: Recombinant Sendai viruses were prepared which cannot express their Cprime, C, or Cprime plus C proteins due to mutation of their respective start codons ([Cprime-minus], [C-minus] and [double mutant], respectively). The [Cprime-minus] and [C-minus] stocks were similar to that of wild-type (wt) virus in virus titer and plaque formation, whereas the double-mutant stock had a much-reduced PFU or 50% egg infective dose/particle ratio and produced very small plaques. Relative to the wt virus infection, the [Cprime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 39 publications
3
25
2
Order By: Relevance
“…Similar but distinct conclusions were drawn by Garcin et al (42). They succeeded in generating a series of recombinant viruses that do not express a subset of C proteins or that express the C proteins with a mutation of a single amino acid change, but failed to isolate four-Cknockout virus (69). Not only a double mutant similar to C/C'( -) virus but also C -virus, which was generated by mutations of the initiation codon AUG I 14 to GCG 11 \ lost the inhibitory effect on IFN-~-stimulated induction of Stat I and on establishment of anti-VSV state.…”
Section: Involvement Of the C Proteins In Blocking Ifn Signalingsupporting
confidence: 56%
See 1 more Smart Citation
“…Similar but distinct conclusions were drawn by Garcin et al (42). They succeeded in generating a series of recombinant viruses that do not express a subset of C proteins or that express the C proteins with a mutation of a single amino acid change, but failed to isolate four-Cknockout virus (69). Not only a double mutant similar to C/C'( -) virus but also C -virus, which was generated by mutations of the initiation codon AUG I 14 to GCG 11 \ lost the inhibitory effect on IFN-~-stimulated induction of Stat I and on establishment of anti-VSV state.…”
Section: Involvement Of the C Proteins In Blocking Ifn Signalingsupporting
confidence: 56%
“…Although gene expression, replication and cytopathogenicity of recombinant V-knockout (V( -)) virus in cell lines were either potentiated or comparable to those of wild type virus, the V( -) virus was strikingly attenuated in capacity of in vivo replication and pathogenicity (24,58). Knockout of the C gene more severely affected virus growth (50,67,69). Two types of mutants were generated; C/C'( -) virus, which does not express C and C' but does express Y1 and Y2, and 4C( -) virus, which does not express any of four C proteins (50,67).…”
Section: Knockout Of the Accessory Protein Attenuates Virus Pathogenimentioning
confidence: 99%
“…Recombinant viruses defective in C expression have been generated for several species, demonstrating that C is dispensable in cell culture (95,96). However, many of these C-deficient viruses demonstrated altered growth characteristics and attenuation in vitro (84,97,98), and all of them were attenuated in animal models, indicating that C proteins are virulence factors (82,98).…”
Section: Coding Strategy Of the P Genes Of Rubulavirusesmentioning
confidence: 99%
“…SeV C protein was initially recognised as a downmodulator of viral mRNA synthesis by using synthetic mini-genomes as templates. 68,69 More direct support for this down-regulatory role of C proteins came from the observations that infections of C ( ), C( ) and C/C ( ) viruses created by Latorre et al 66 and our 4C( ) all accumulated significantly more viral transcripts late in infection, compared with the wild-type infection. The C( ) overexpressed Y1 and Y2, and the C/C ( ) overexpressed Y2, but Y1 and Y2 did not appear to be able to replace C and/or C for downregulation of transcription.…”
Section: Important Contribution To Both In Vitro Replication and In Vmentioning
confidence: 69%
“…65 The results conclusively demonstrated that C proteins greatly contribute to full replication of SeV but can be categorised as nonessential gene products. Failure to isolate 4C( ) viruses by Latorre et al 66 might be simply due to a low efficiency of their virus rescue system.…”
Section: Important Contribution To Both In Vitro Replication and In Vmentioning
confidence: 99%